Evaluation of Performances of Cowpea (Vigna ungiculata) Genotypes in Agronomy Farm of Lamjung Campus - Bhattarai, Chandan; Marasini, Dinesh; Dawadi, Prabin; Aryal, Sadkishya (International Journal of Applied Sciences and Biotechnology, 2017)
Seed to seed production experiments for cowpea (Vigna ungiculata) was conducted at Agronomy farm at IAAS Lamjung, and to compare production potentialities of given cowpea genotypes under the given sets of conditions. The treatment consists of two cowpea varieties viz. Prakash (Standard Check) and Malepatan (Local check) and four genotypes; IT 99K-573-2-1, IT 86F-2062-5, IT 93K-452-1, IT 98K-205-8. The experiment was conducted on RCBD design. .All other activities were carried out according to prepared working calendar almost from August 2016 to December 2016. Data collection were done for pre-determined growth and other yield parameters and was analyzed using MSTAT. Major parameters were Grain yield, Seeds/plant, Pods/plant, plant height, pod length, harvest index and test weight. Result shows maximum grain yield and harvest index was found for Prakash (Standard Check).Plant height and Pods /Plant was found highest for IT 99K-573-2-1. Similarly highest seed weight was found for Prakash (Standard Check) and Seeds/Plant and Pod length was maximum for IT 86F-2062-5. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 382-385